Association between thermal inversion and cognitive trajectories among middle-aged and older adults in CHARLS: A latent class trajectory analysis - Kai Liu; Jing Wang; Junru Wang; Yue Yang; Yali Wang; Jiahui Zhang; Xiaojun Ma; Zhuoyuan Li; Ping Chen; Jiangping Li (PLoS ONE, 2025)
Background Previous studies have demonstrated that cognitive decline is related to meteorological conditions, but most of them focus on air pollutants rather than thermal inversion (TI). The impact of TI on cognitive function remains unclear. Therefore, this study aims to explore the role of TI in the changes of cognitive function trajectories. Methods This study included 5,762 participants aged 45 years and older from China Health and Retirement Longitudinal Study (CHARLS) between 2011−2015. The latent class trajectory model (LCTM) was used to fit population trajectories of cognitive development. The TI data were obtained from NASA’s MERRA-2 dataset, which were totaled by comparing temperatures of atmosphere. The multinomial logistic regression model and restricted cubic spline (RCS) were used to assess the relationship between TI and cognition, the primary outcome was class membership in cognitive trajectories estimated by LCTM. Results There were three trajectories of cognitive development in 5,762 participants, which were categorized into three trajectories: U-shaped (decline then improvement), Slowly decline and N-shaped (improvement then decline). In the Slowly decline class, the proportion of individuals exposed to moderate and high levels of TI was the highest. After adjusting for covariates, at medium TI exposure, the odds of being classified into the Slowly decline trajectory versus the U-shaped trajectory were 26.9% higher (OR=1.269, 95% CI = 1.054 ~ 1.528, P = 0.012), at high exposure, 47.8% higher (OR=1.478, 95% CI = 1.152 ~ 1.895, P = 0.002). Conclusion Higher TI exposure was associated with trajectory membership patterns indicative of worse cognition, strategies that reduce TI exposure may support healthier cognitive trajectories.